Способ получения карбамидоформальдегидных смол - Алексеев В. Е. Вячеслав Евгеньевич; Ерофеев В. И. Владимир Иванович; Горностаев В. В. Виктор Викторович; Кондрашкин П. Н. Петр Николаевич; Леонтьев С. П. Сергей Павлович; Димитров А. М. Александр Михайлович; Шишов А. В. Анатолий Викторович; Куренев С. В. Сергей Владимирович
опубл. 20.04.07